THE IMPACT OF GOOD CORPORATE GOVERNANCE AND ENTERPRISE RESOURCE PLANNING ON FINANCIAL PERFORMANCE - Laeli, Septi Nur; Fatikhatur Riziqiyah, Metiya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study examines how Good Corporate Governance (GCG) and the implementations of Enterprise Resource Planning (ERP) system affect financial performance (NPM, OPM). The analysis concentrated on manufacturing firms in the food and beverage subsector that were listed between 2020 and 2024 on the Indonesian Stock Exchange (IDX). Using purposive sampling, 41 companies being selected as samples, with a total of 205 observations. Secondary data was analyzed using panel data regression in Eviews 10. The results showed that GCG had no positive significant effect on NPM, GCG had no positive significant effect on OPM, the implementation of ERP had a positive significant effect on NPM, the implementation of ERP had a positive significant effect on OPM and simultaneously GCG and ERP use had a significant effect on NPM and OPM.